Prehypertension in early pregnancy is a risk factor for hypertensive disorders during pregnancy: A historical cohort study in Japan - Takeshi Nagao; Keisuke Saito; Michiko Yamanaka (Taylor & Francis Group, 2021)
Objective: We evaluated the association between pre-hypertension (120-139 or 80-89 mmHg) in early pregnancy, hypertensive disorders of pregnancy (HDP), and perinatal adverse outcomes. Methods: We included 14,066 pregnant women, treated between 2003 and 2019 in Japan. Based on a blood pressure chart review recorded before 20 weeks of gestation, we stratified participants into the prehypertension (n = 3,806) and normotensive (n = 10,260) groups. Results: Prehypertension, an independent risk factor for HDP in the multivariate analysis (P< 0.001), was significantly associated with preterm and small-for-gestational age infants. Conclusion: Prehypertension potentially confers a risk for adverse perinatal outcomes in apparently normal pregnancies.